The proposal of the sustainable development inwards of scienntific works of Professor Stephen Kozłowski - Skowroński, Antoni (Studia Ecologiae et Bioethicae, 2010)
The article is connected with the life and scientific works of Professor Stephen Kozlowski died in September 2007. He was a great research scientist working with the geology of raw materials and then with the conservation and formation of natural environment. Last 25 years of his scientific work he was engaged in the creation of the concept of sustainable development and in the promotion of the concept in Polish social, economic and political life. Using the term “sustainable development” he meant all the activities which improve man’s life conditions and which do not cause the degradation of natural environment. Such effect can be obtained by equalizing of three development vectors: natural, economic and cultural. He proposed that Poland should adapt the economic progress to natural conditions of environment. He said that the idea of the sustainable development being based on the foundations of ecological era had all chances to make a success in our conditions of weather, soil, water and raw minerals.